Eosinophilic endotype of chronic obstructive pulmonary disease: similarities and differences from asthma - Andrew Li (The Korean Association of Internal Medicine, 2021)
Approximately 25% to 40% of patients with chronic obstructive pulmonary disease (COPD) have the eosinophilic endotype. It is important to identify this group accurately because they are more symptomatic and are at increased risk for exacerbations and accelerated decline in forced expiratory volume in the 1st second. Importantly, this endotype is a marker of treat ment responsiveness to inhaled corticosteroid (ICS), resulting in decreased mortality risk. In this review, we highlight differences in the biology of eosinophils in COPD compared to asthma and the different definitions of the COPD eosinophilic endotype based on sputum and blood eosinophil count (BEC) with the corresponding limitations. Although BEC is useful as a biomarker for eosinophilic COPD endotype, optimal BEC cut-offs can be combined with clinical characteristics to improve its sensitivity and specificity. A targeted approach comprising airway eosinophilia and appropriate clinical and physiological features may improve identification of subgroups of patients who would benefit from biologic therapy or early use of ICS for disease modification.